Large-Scale Genetic Perturbations Reveal Regulatory Networks and an Abundance of Gene-Specific Repressors - Kemmeren, Patrick; Sameith, Katrin; van de Pasch, Loes A.L.; Benschop, Joris J.; Lenstra, Tineke L.; Margaritis, Thanasis; O’Duibhir, Eoghan; Apweiler, Eva; van Wageningen, Sake; Ko, Cheuk W.; van Heesch, Sebastiaan; Kashani, Mehdi M.; et al. (Cell, 2014)
To understand regulatory systems, it would be useful to uniformly determine how different components contribute to the expression of all other genes. We therefore monitored mRNA expression genome-wide, for individual deletions of one-quarter of yeast genes, focusing on (putative) regulators. The resulting genetic perturbation signatures reflect many different properties. These include the architecture of protein complexes and pathways, identification of expression changes compatible with viability, and the varying responsiveness to genetic perturbation. The data are assembled into a genetic perturbation network that shows different connectivities for different classes of regulators. Four feed-forward loop (FFL) types are overrepresented, including incoherent type 2 FFLs that likely represent feedback. Systematic transcription factor classification shows a surprisingly high abundance of gene-specific repressors, suggesting that yeast chromatin is not as generally restrictive to transcription as is often assumed. The data set is useful for studying individual genes and for discovering properties of an entire regulatory system. [Display omitted] •A systems analyses resource reports expression signatures for 1,484 yeast gene knockouts•Analysis reveals pathway branching, connectivity, and responsiveness to perturbations•Four feed-forward loop types are overrepresented in the genetic perturbation network•Transcription factor classification shows an abundance of gene-specific repressors A comprehensive mRNA expression profiling study reports the effects of over 1,400 individual gene deletions in yeast, focusing on nonessential regulators of gene expression. Analysis of the data indicates a surprisingly high abundance of repressors, suggesting that chromatin itself may not be generally restrictive to transcription, as previously supposed.